(untitled) (Web of Teachers: Inderscience Research, 2024)
The article describes the conceptual ideas aimed at forming the methodological competence of future history teachers. The importance of general methodological and specific methodological knowledge in the preparation of future history teachers for professional activity is highlighted. It is stated that the study of the methodology of teaching history in modern conditions has a practice-oriented character and is an important component of the professional training of a history teacher.